2011
DOI: 10.1111/j.1365-2133.2011.10270.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy reduces the histological features of actinic damage and the expression of early oncogenic markers

Abstract: These findings show that PDT has the potential to reduce the histological signs of photoageing. Moreover, the reduction of Ki-67, a marker of proliferation and of p53, a marker of early skin carcinogenesis, indicates a reversal of the carcinogenic process. On the other hand, the fact that one treatment does not clear dysplasia and expression of p53 completely, and the persistence of cyclin D₁, indicate that one single treatment, despite showing good clinical results, is not sufficient to clear completely the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 42 publications
(52 reference statements)
1
45
2
Order By: Relevance
“…5-Fluorouracil, diclofenac, and topical imiquimod are alternatives following this approach strategy to these lesions [4]. After treatment with photodynamic therapy histological evaluation demonstrated an ability to reduce the histological signs of photodamage, reducing the proliferation marker Ki-67 and p53 marker of early carcinogenesis [8]. Interestingly, despite the improvement of the basal keratinocytes dysplasia, as assessed by scale of two different observers, in 45% of cases, there was still some degree of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…5-Fluorouracil, diclofenac, and topical imiquimod are alternatives following this approach strategy to these lesions [4]. After treatment with photodynamic therapy histological evaluation demonstrated an ability to reduce the histological signs of photodamage, reducing the proliferation marker Ki-67 and p53 marker of early carcinogenesis [8]. Interestingly, despite the improvement of the basal keratinocytes dysplasia, as assessed by scale of two different observers, in 45% of cases, there was still some degree of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have shown that PDT can reverse actinic skin damage in terms of reducing epidermal expression of immunohistochemical markers of dysplasia, p53, and Ki-67 (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Bagazgoitia et al [18] showed the potential for PDT to reduce actinic damage and elastosis, and to significantly decrease the expression of Ki-67 and TP53. The expression of cyclin D1 remained stable.…”
Section: Discussionmentioning
confidence: 99%